Development of an early intervention guidebook for students with physical disabilities as special education students learning support - Endang Pudjiastuti Sartinah; S. Sujarwanto; Diah Anggraeny; Endang Purbaningrum; Faizur Rahmatin (Research and Development in Education (RaDEn), 2025)
Students with physical disabilities often face barriers in accessing appropriate early intervention resources within special education settings. This study focuses on addressing the lack of structured and accessible guidebooks designed specifically to support early intervention for these students. The research aimed to develop an early intervention guidebook tailored for students with physical disabilities to enhance the quality and effectiveness of their learning support. Employing a Research and Development (R&D) approach with the ADDIE model, this study involved stages of needs analysis, design, development, and evaluation. Data were collected through expert validation and usability testing, analyzed using a combination of quantitative and qualitative methods. The findings indicate that the developed guidebook is highly valid and usable, highlighting its potential as a critical tool to bridge the gap in early intervention resources for students with physical disabilities in special education programs.